2006
DOI: 10.1158/1055-9965.epi-06-0504
|View full text |Cite
|
Sign up to set email alerts
|

APC E1317Q Is Not Associated with Colorectal Cancer in a Population-Based Case-Control Study in Northern Israel

Abstract: A variant in the adenomatous polyposis coli gene, APC E1317Q, has been inconsistently associated with risk of colorectal cancer. We used data collected as a part of the Molecular Epidemiology of Colorectal Cancer study, a population-based study of colorectal cancer in northern Israel (1,834 matched cases and controls), to evaluate the relationship between this variant and risk of sporadic colorectal cancer. There was no association between E1317Q and colorectal cancer [odds ratio (OR), 1.15; 95% CI, 0.65-2.02]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We also found a single TINF2 S245Y variant that is associated with dyskeratosis congenita. The likely benign variant APC E1317Q was observed in two cases (Rozek et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…We also found a single TINF2 S245Y variant that is associated with dyskeratosis congenita. The likely benign variant APC E1317Q was observed in two cases (Rozek et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies(3143) have focused on four germline missense variants, i.e., APC I1307K, E1317Q, D1822V and G2502S, of which, APC I1307K(32, 44) and APC E1317Q(31) are founder mutations in Ashkenazi Jews and have a rare prevalence (minor allele frequency (MAF) of < 1 percent) in non-Hispanic Whites (3336). In Askenazim, APC I1307K (MAF=6%) is associated with risk of colon cancer without the corresponding polyposis seen in FAP patients(32, 44) and APC E1317Q(31) is associated with colorectal tumors in some but not all studies (38, 39). In non-Hispanic white populations, the remaining two reported APC SNPs, D1822V and G2502S, have a MAF of 22.5% and 2.5%, respectively (120 HapMap representative European ancestry panel).…”
Section: Introductionmentioning
confidence: 99%
“…The c.3949G>C mutation is significantly associated with colorectal adenomas and carcinomas [42,52]. Some study showed that there was no association between Glu1317Gln and colorectal cancer [53][54][55].…”
Section: Discussionmentioning
confidence: 99%